Rhabdomyolysis and multiple peripheral neuropathies in lower legs following heavy alcohol abuse: case - 김바울; 김태희; 이신우; 이주강; 박기덕; 임오경 (대한근전도 전기진단의학회지, 18(1), 2016)
We report on a 44-year-old man with multiple peripheral neuropathies who developed bilateral lower extremity weakness. After heavy alcohol abuse, he experienced pain in both lower legs and severe erythematous swelling. The initial laboratory test suggested non-traumatic rhabdomyolysis caused by a heavy alcohol binge. Magnetic resonance images showed edema in the bilateral gluteus minimus and medius, pyriformis, and anterior calf muscles. The electrodiagnostic study showed bilateral sural, tibial, and peroneal neuropathies. In conclusion, in patients with acute and chronic alcohol abuse state, multiple neuropathies can be caused by integration of immobilization, electrolyte imbalance, compression, and direct myotoxicity. The patient began gait training with bilateral UD-flex orthosis with crutches. He was trained to use the crutches safely and an electrical stimulation test (EST) was applied. He was able to walk outdoors. We suggest consideration of early diagnosis and appropriate rehabilitative management to prevent severe secondary complications such as neuropathy. KCI Citation Count: 0